GAMBARAN PSYCHOLOGICAL WELL-BEING MANTAN NARAPIDANA - Azani, Azani (EMPATHY Jurnal Fakultas Psikologi, 2012)
AbstractThis study aims to describe the dimensions of psychological well-being of former inmates. Study was conducted in one of the areas in Yogyakarta Special Province, the City of Yogyakarta. The approach used in this study is a case study. The method of data collection used interviews and observations. The subjects of this study are 3 participants. The data analysis that used in this study is content analysis. Based on the research, subject A has not shown self acceptance dimension, but on the subject of B and C have shown the existence of self-acceptance, when the subject was shown a positive relationships with others, the dimensions of autonomy has not been demonstrated by the three subjects, the subjects A and B has not shows the dimensions of environmental mastery, but the subject of C have shown these dimensions, three subjects have shown the dimension of interest, and three subjects has also shown the dimension of personal growth.Keywords : psychological well being, ex-convict